Synthesis and Spectral Properties of Porphyrin-Cored Arylether Dendrimers with Hydroxy Peripheral Groups - Lim, So-yeon; Choi, Daeock; Shin, Eun J. (Letters in Organic Chemistry, 2013)
Free base porphyrin-cored arylether dendrimers 2a∼2c with terminal hydroxy groups in the periphery have been successfully prepared by hydroboration-oxidation reaction of corresponding 1a∼1c with terminal vinyl groups in the periphery. Their zinc derivatives Zn-2a∼Zn-2c have also been prepared. Absorption and fluorescence properties of 2a∼2c and Zn-2a∼Zn-2c with peripheral hydroxy groups were affected more by dendritic environments than 1a∼1c and Zn- 1a∼Zn-1c with peripheral vinyl groups.
Keywords: hydroxy group